PENTINGNYA PENDIDIK KRISTEN MEMILIKI KEPRIBADIAN YANG UNGGUL DI PERGURUAN TINGGI - Purba, Asmat (Jurnal TEDC; Vol 18 No 3 (2024): JURNAL TEDCDO - 10.70428/tedc.v18i3.865, 2024)
This article discusses the importance of Christian educators having a superior personality in college. The approach taken to discuss this issue is theological, reflective and applicative. After discussing the duties of Christian educators, the author elaborates on how the superior personality has a positive influence on students on campus. The obstacles to not having a superior personality are also discussed, especially the success of character formation, self-concept, and character building strategies of a Christian educator. In the final part, this article discusses proposals on how to make an educator have a superior personality.